Intervenção e influência norte-americana sobre a cultura e educação japonesa e brasileira no Pós-Segunda Guerra Mundial: o despertar da memória pela oralidade - Mello, Valéria Maria Sampaio (2006)
This study is about the cultural and educational reform which happened in Japan after the World War II, in comparison to the Brazilian experience, at the same time, i.e. it is about the impact this has caused to Japan, when of the occupation of the armed forces by the Americans, as well as the cultural influence Brazil has gone through, more specifically the city of Fortaleza, both the country and the city have been under direct influence by the North Americans at the same time. The objective of the period chosen is to trace back the threads that wove the individual formation proposition of niponic nationality in the years that followed the W W II. Special emphasis was given to the way the people of the time, who have lived this reform implemented in Japan under military occupation, as well as to the rebuilding of the cultural atmosphere lived in Fortaleza then, in relation to the North American hegemony. This research is based on historiographic, journalistic and oral resources, to place us in the historical period. It highlights the memory of the people who have lived this specific period in order to compare accounts and remembrances to establish connections between the historiographic material and the empirical evidences. This study shows the historical moment in which both the Japanese and Brazilian cultures have assimilated some values based in Western material capitalism, through the consumption and “way of life” of the United States of America to the detriment of their own spiritual and cultural values. This confrontation between Japan and Brazil have brought to the surface some distinct traditions and historical costumes and it is limited to the understanding of the cultural changes which have happened in the two countries under the influence of the North America, which are expressed here amidst the evidences of the strong emotional impact they have caused in our Japanese witnesses.